Untranslatability as Historical Chronotope. Cassin, B., & Sigov, C. (Eds.). (2024). European Dictionary of Philosophies: Ukrainian Context. Lexicon of Untranslatables. Chapter VII (Vol. V, pp. 215-248). Kyiv: Duh i Litera. - Chukhrai, Elvira (Sententiae, 2024)
Review of Chapter VII “Language, Culture, Historyˮ from Volume V of the European Dictionary of Philosophies (Kyiv: Duh i Litera, 2024).